Analisis Pengaruh Dow Jones Islamic Market Asia/Pacific Ex-Japan (DJIP2), Dow Jones Arabia Titans 50 (DJARB50), Harga Emas Dunia, dan Nilai Kurs Terhadap JII Tahun 2016-2018 - M. Asri Setiawan (Institut Agama Islam Negeri Kendari, 2019)
This study aims to find out empirically the influence Dow Jones Islamic Market Asia/Pacific ex-japan (DJIP2), Dow Jones Arabia Titans 50 (DJARB50), World Gold Price, Exchange Rate on the Jakarta Islamic Index (JII) movement. This research uses quantitative research methods, using multiple linear regression analysis models. Data collection uses secondary data from documentation related data. Data is taken from the monthly closing price of each variable from 2016-2018 (36 months). The research test uses the t test and F test and is processed using SPSS16. The results showed that DJIP2, DJARB50, and exchange rates had a significant effect on JII both partially and simultaneously while the world gold price did not have a significant effect on JII partially but simultaneously had a significant effect on JII.